2022
DOI: 10.1159/000520501
|View full text |Cite
|
Sign up to set email alerts
|

AXL and MET in Hepatocellular Carcinoma: A Systematic Literature Review

Abstract: <b><i>Background:</i></b> Multikinase inhibitors (MKIs) have been shown to improve survival in patients with hepatocellular carcinoma (HCC) compared with placebo. Distinct from other MKIs, cabozantinib has inhibitory activity for both AXL and MET. This review considers the literature elucidating the role of AXL and MET in HCC progression, treatment resistance, and immunomodulation. A systematic search of the PubMed database was conducted on November 16, 2020, and identified a total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 94 publications
(158 reference statements)
1
10
0
Order By: Relevance
“…Overexpression of MET is seen with sorafenib treatment, suggesting that increased activation of the MET pathway contributes to sorafenib treatment resistance in patients with HCC 11,12 . Cabozantinib is a multiple RTK inhibitor targeting RTKs implicated in tumor growth, metastasis, and angiogenesis, including MET, vascular endothelial growth factor receptor 2, RET, AXL, KIT, and TIE‐2 10,13 . The pivotal phase III CELESTIAL study enrolled more than 700 patients with advanced HCC previously treated with sorafenib across 19 countries 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of MET is seen with sorafenib treatment, suggesting that increased activation of the MET pathway contributes to sorafenib treatment resistance in patients with HCC 11,12 . Cabozantinib is a multiple RTK inhibitor targeting RTKs implicated in tumor growth, metastasis, and angiogenesis, including MET, vascular endothelial growth factor receptor 2, RET, AXL, KIT, and TIE‐2 10,13 . The pivotal phase III CELESTIAL study enrolled more than 700 patients with advanced HCC previously treated with sorafenib across 19 countries 14 .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Cabozantinib is a multiple RTK inhibitor targeting RTKs implicated in tumor growth, metastasis, and angiogenesis, including MET, vascular endothelial growth factor receptor 2, RET, AXL, KIT, and TIE-2. 10,13 The pivotal phase III CE-LESTIAL study enrolled more than 700 patients with advanced HCC previously treated with sorafenib across 19 countries. 14 CELESTIAL results indicated a significant survival benefit with cabozantinib versus placebo in patients with advanced HCC, with a 24% reduction in the relative risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the presence or absence of an interaction between cabozantinib and RT could not be ensured before the study; therefore, the current study did not explore the possible mechanism. However, the lines of evidence provide the rationale for radiosensitization with cabozantinib for RT [ 11 , 15 , 30 , 32 , 52 , 53 ]. Further studies to detect the possible mechanism in vivo and in vitro are warranted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of MET and AXL helps overcome resistance to agents that target the VEGF receptor pathway. 7 The CELESTIAL phase 3 trial demonstrated a significant survival benefit with cabozantinib versus placebo in patients previously treated with sorafenib. 6 However, sorafenib is no longer recommended as the first-line chemotherapy and the effectiveness of cabozantinib in different situations that occur frequently in real-world practice has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%